Audit Committee Effectiveness and Corporate Financial Performance in Listed Nigerian Manufacturing Firms - Irowa-Omoregie, Osasogie; Ohonba, Nosa (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
Corporate governance is essential for financial stability and operational efficiency, with audit committees serving as a key oversight mechanism. This study examines the relationship between audit committee effectiveness and corporate financial performance, focusing on scale efficiency in Nigerian manufacturing firms. Using panel data from 49 listed manufacturing firms between 2012 and 2022, the study employs regression analysis to evaluate the impact of audit committee size and independence on scale efficiency. The findings reveal that audit committee size has a negative but insignificant effect on scale efficiency, suggesting that increasing committee size does not necessarily improve financial performance. Similarly, audit committee independence shows an insignificant relationship with scale efficiency, indicating that independence alone does not enhance operational efficiency. However, among the control variables, leverage exhibited a significant negative effect on scale efficiency, underscoring the influence of a firm’s financial structure on its operational performance. The study underscores the need for stronger governance enforcement and emphasizes that firms should prioritize expertise over structural attributes. Further research should explore additional governance factors influencing financial performance in Nigerian manufacturing firms.